2012
DOI: 10.1002/cyto.a.22220
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CD90 and CD14 stem cell markers in malignant breast cancer cell lines

Abstract: The recently emerged concept of cancer stem cell (CSC) has led to a new hypothesis on the basis for tumor progression. Basically, the CSC theory hypothesizes the presence of a hierarchically organized and relatively rare cell population, which is responsible for tumor initiation, self-renewal, and maintenance, in addition to accumulation of mutation and resistance to chemotherapy. CSCs have recently been described in breast cancer. Different genetic markers have been used to isolate breast CSCs, none of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 42 publications
1
28
0
1
Order By: Relevance
“…Although CD90's exact function is currently unknown, it has been implicated to have a significant role in cellular adhesion and migration, regulating cell-cell and cell-matrix interactions [31]. Besides its expression on certain normal cell types, CD90 has been described as a CSC marker in various malignancies, such as hepatocellular carcinoma, esophageal cancer, glioma, and lung and breast cancers [16][17][18][19][20]. In this study, we demonstrated for the first time that CD90 also appears to be a potential CSC marker for INS, because CD90…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CD90's exact function is currently unknown, it has been implicated to have a significant role in cellular adhesion and migration, regulating cell-cell and cell-matrix interactions [31]. Besides its expression on certain normal cell types, CD90 has been described as a CSC marker in various malignancies, such as hepatocellular carcinoma, esophageal cancer, glioma, and lung and breast cancers [16][17][18][19][20]. In this study, we demonstrated for the first time that CD90 also appears to be a potential CSC marker for INS, because CD90…”
Section: Discussionmentioning
confidence: 99%
“…CD90 demonstrated to be such a marker, as CD90-positive INS cells demonstrated a more tumorigenic behavior in vivo compared with CD90-negative INS cells. CD90 is a glycosylphosphatidylinositol (GPI)-anchored glycoprotein that has been correlated with the tumorigenicity of hepatocellular carcinoma, esophageal cancer, glioma, and lung and breast cancers [16][17][18][19][20]. On top of that, through binding to avb3 integrin, CD90 has been implicated to facilitate metastasizing behavior in melanomas, by establishing an intimate connection between melanoma cells and activated endothelium [21].…”
mentioning
confidence: 99%
“…In breast cancer, CD90 was expressed in highly metastatic breast cancer cell lines MDA-MB-231 [109] and Hs578-T and had an inverse correlation with CD14, which is usually expressed in non-metastatic cell lines [14]. In breast tumor samples (24 samples), CD90 was co-expressed highly with CD44 in cancer cells and high CD90 was also seen in CD44 negative intra-tumor stromal cells [110].…”
Section: Cd90 Regulates Metastasismentioning
confidence: 98%
“…CD90 is a GPI-anchored cell surface protein which is involved in cell-cell and cell-matrix interaction and has been implicated in several cancers. In many cancers, CD90 expression identifies the cancer stem cells [7][8][9][10][11][12][13] and overexpression in the tumor microenvironment promotes cancer proliferation and dissemination [3,14,15]. In others, CD90 expression causes inhibition of tumor invasion and anchorage independent growth [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…cells demonstrate self-renewing properties as well as higher tumor-promoting capacity and cell proliferation ability [32,33]. In different breast cancer cell lines, CD90 was found to be highly expressed in the malignant cell lines [34]. Moreover, in many different tumors CD90 was proposed to be a cancer stem cell marker and a possible target for the diagnosis and therapy of the malignancies [35][36][37].…”
Section: Discussionmentioning
confidence: 98%